Molecular and Cytogenetic Study of East African Highland Banana - Němečková, Alžběta; Christelová, Pavla; Čížková, Jana; Nyine, Moses; Van den houwe, Ines; Svačina, Radim; Uwimana, Brigitte; Swennen, Rony; Doležel, Jaroslav; Hřibová, Eva (Frontiers in Plant Science, 2018)
East African highland bananas (EAHB) are staple food crop in Uganda, Tanzania, Burundi and other countries in the African Great Lakes region in Africa. Even though several morphologically different types exist, all EAHB are triploidandtriploid and display minimal genetic variation. To provide more insights into the genetic variation within EAHB, genotyping using simple sequence repeat (SSR) markers, molecular analysis of ITS1-5.8S-ITS2 region of ribosomal DNA locus and the analysis of chromosomal distribution of ribosomal DNA sequences was done. A total of 40 triploid EAHB accessions that were available in the Musa germplasm collection (International Transit Centre, Leuven, Belgium) were characterized. Six diploid accessions of M.Musa acuminata ssp. zebrina, ssp. banksii and ssp. malaccensis representing putative parents of EAHB M. acuminata ssp. zebrina, ssp. banksii and ssp. malaccensis were included in the study. Flow cytometric estimation of 2C nuclear DNA content revealed small differences (max ~ 6.5 %) in genome size among the EAHB clones. While no differencedifferences in the number of 45S and 5S rDNA loci waswere found, genotyping using 19 SSR markers resulted in grouping the EAHB accessions into four clusters. DNA sequence analysis of the ITS region suggestedindicated a relation of EAHB clones with MusaM. acuminata and, surprisingly, also with M. schizocarpa. The results suggest that EAHB cultivars originated from a single hybrid clone with M. acuminata ssp. zebrina and ssp. banksii being its most probable parents. However, M. schizocarpa seems to have contributed to the formation of this group of banana.